Proyeksi Konsep Pedoman Pemidanaan Dalam Sistem Peradilan Pidana Di Indonesia: Telaah Perbandingan Hukum Dengan Amerika Serikat - Lathof, Muhammad Zuhal Qolbu; Fitriasih, Surastini (Nagari Law Review, 2024)
Since 2020, the criminal justice system in Indonesia has been awarded two sentencing guidelines which can be found in Supreme Court Regulation Number 1 of 2020 concerning Sentencing Guidelines Article 2 and Article 3 of the Corruption Eradication Law and Articles 53 to 56 of the National Criminal Code. However, based on the Academic Text of the National Criminal Code, it is stated that the term sentencing guidelines is a term that is still open to review, because it contains various meanings, so it is still open to developing the term. This article discusses the projection of the concept of sentencing guidelines in the criminal justice system in Indonesia by establishing an independent state institution that has the authority to create and evaluate a sentencing guideline such as the United States Sentencing Commission (USSC) which applies in the criminal justice system in the United States by using law comparative method. The research results show that the concept of sentencing guidelines in Indonesia and the United States both have a rationale for responding to the phenomenon of sentencing disparities and the two countries have their own methods. There are similarities and differences between the sentencing guidelines in Indonesia and the United States. In the equation there is one variable, namely, the variable of the judge's relationship with the sentencing guidelines. Then, in the differences section there are four variables, namely, orientation variables, institutions or stakeholders, form and scope. Then, regarding the need for the formation of an independent state institution that has the authority to create and evaluate a sentencing guideline, it becomes rational in the criminal justice system in Indonesia because predictability in imposing a range of sentences is a fulfillment of the value of law certainty, so that the more the sentence can be predicted, the greater the law certainty for convicts can be fulfilled. Apart from that, this independent state institution also has the authority to provide recommendations to legislators regarding the rationalization of the range of sentences imposed which so far has not been properly rationalized